English for Agriculture Vocational School Students: A Need Analysis Study at SMK Negeri 2 South Bengkulu - Desi Veranita; Syahrial Syahrial; Irwan Koto (Universitas Bengkulu, 2017)
This research was aimed to identify the need of the students of agriculture study program on English materials. This research focused in find out the most important English skills and Sub-Skills for the students of agriculture study program and find out the English topics are needed for the students of agriculture study program at SMK Negeri 2 South Bengkulu. The research used mix method (combine both qualitative and quantitative method). This research was conducted in Agriculture Vocational School 2 South Bengkulu (SMK Negeri 2 South Bengkulu). The data was taken from the assistance of curriculum, the English teachers, productive teachers and the alumni of SMK Negeri 2 South Bengkulu. The data was collected by using questionnaire and interview. The result of the research shows that: first, the most important English skills for the students of agriculture study program at SMK Negeri 2 South Bengkulu are Speaking and Reading Skills. Reading sub-skills classified as; reading in general comprehension, understanding the plan of the text, guessing the meaning of unfamiliar words, do skimming and scanning activities and understanding the organization of the text. Speaking sub-skills classified as; speaking with fluency, attention of choice and pronunciation and using the correct ways/ manners of speaking. Second, English topics for the students of agriculture were the English topics related to the agriculture term. The topics of reading were; reading the text of part of plants, reading the text of the technique of maintenance of plants and operating hart equipment farming. The topics of speaking were; do direct conversations related to agriculture terms, presenting the report of filed productive practice, describing of how to operate hard equipment farming and maintenance of the plants.